Un exemple de créativité ordinaire au bénéfice d’une dynamique inclusive - Olivier Kheroufi-Andriot (Éducation et Socialisation)
A young child boarding in a Therapeutic, Educational and Pedagogical Institute (ITEP) is again enrolled in an elementary school class in the so-called "ordinary" school environment, and the purpose of this article is to highlight "little things » deployed by the actors registered in this situation of inclusion. We hypothesize that these feed an inclusive dynamic for the benefit of its inclusion journey, and that they bring out an ordinary creativity to be included. Without idealizing this question of creativity, our research offers a perspective for (re)thinking it.